Overview of the Development of Graphene Aerogel as an Anode Material in Lithium-Ion Batteries - Neneng Andriani Joko; Sahidin; Ahmad Zaeni; Ruslan (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The increasing need for energy storage along with the development of portable electronic devices and electric vehicles is driving the development of lithium-ion battery (LIB) anode materials with higher and sustainable electrochemical performance. Commercial graphite currently used as an anode still has limitations in the theoretical capacity and kinetics of lithium ion diffusion. Graphene aerogel (GA), with its porous three-dimensional structure, high surface area, and interconnected conductive network, it has attracted attention as an alternative anode material to improve the specific capacity, velocity and stability of LIB cycles. This review article  was compiled through a literature study of research articles and review articles published in the 2016–2023 range, obtained from reputable scientific databases. The literature was analyzed comparatively to examine the relationship between synthesis methods, structural characteristics, composite formation, and electrochemical performance of graphene aerogel as a LIB anode material. The results showed that the three-dimensional aerogel structure rich in hierarchical pore defects was able to increase the specific capacity to more than 1400 mAh g⁻¹, improve the transport of Li⁺ ions and electrons, and maintain cycle stability at various current densities. The formation of composites with metal oxides or transition metals has also been shown to improve the electrical conductivity and storage capacity of lithium. However, most studies still rely on synthetic graphene or graphene oxide as a precursor, so the sustainability aspect of the material has not been fully integrated. Recent studies on LIB anode graphite recycling show great potential for conversion into high-value-added graphene aerogels, although their application as a battery anode material is still limited. Therefore, future research needs to focus on integrating the LIB anode graphite recycling approach with graphene aerogel synthesis  to produce a high-performance and sustainable anode material.